Juventude e resistência: o funk como forma de expressão dos(das) jovens da periferia - Araujo, Nicole Barbosa de (2018)
Understanding the relation between black and poor youth from the periphery with leisure and culture, through the artistic and cultural universe of funk is the purpose of this study. In this way, the discussion regarding the constitution and current reality of the periphery will be privileged, considering the racial questions as a structuring element of Brazilian capitalism, and also the implantation of the neoliberal agenda in Brazil, a project continued by the PT governments, during the thirteen years they remained in power. From such analysis, a debate about the daily life of the youth of the periphery will be proposed, and elements that amplifies the reflection over the cultural expressions from young people, entering into the diversity of funk’s universe, ranging from the style "ostentação" and "proibidão", until the "funk consciente" and the one that sings the resistance of transsexual women. The concept of youth and the elements for a reflection over work’s educational dimension of the Social Worker next to periphery’s youth also will be discussed. The dissertation also contemplates an analysis of the realization of a Focus Group with young people at the city of Itapevi, who presented several considerations about the daily life from the young people and from the funk universe